Whether interstitial space features were the main factors affecting sediment microbial community structures in Chaohu Lake - Lu, Xiang; Zhou, Xiaotian; von Sperber, Christian; Xu, Yaofei; Wei, Zhipeng; Li, Siyan; Ruan, Aidong (Frontiers in Microbiology, 2022)
Sediments cover a majority of Earth’s surface and are essential for global biogeochemical cycles. The effects of sediment physiochemical features on microbial community structures have attracted attention in recent years. However, the question of whether the interstitial space of submerged sediments has significant effects on microbial community structures remains unclear. In this study, based on identified OTUs (operational taxonomic units), we investigated correlations among the interstitial space volume, interstitial gas space, volumetric water content, sediment particle features (average size and evenness), and sediment depth with the microbial community structure in sediments of Chaohu Lake, Anhui Province, China. Our results indicated that sediment depth was the closest one to the main environmental gradient. Then, the destruction effects of gas space on sediment structures can physically affect the community similarities in a site sediment column. However, including gas space, the five interstitial space parameters appeared ineffective in affecting the structures of sediment microbial community in different sediment layers.